Effects of word-of-mouth on the behavior of Austrian blood donors: a case study of the Red Cross Blood Donation Service. (13th December 2017) - Martin, Sebastian; Greiling, Dorothea; Leibetseder, Nina
Summary: The procurement of blood is an essential challenge of today's health care. Current studies emphasize the influence of word-of-mouth (WOM) on health care behavior, including blood donation. Still, there exists no study which systematically investigates how WOM affects the behavior of blood donors. Therefore, this paper aims to contribute to this lack of research by focusing on Austrian blood donors as possible receivers and senders of WOM. A survey was distributed to 300 donors of the Austrian Red Cross with a return of 245 surveys. The results highlight the strong influence of WOM on the awareness of the blood service and the willingness to donate blood. Further, structured and organized procedures, friendly employees and respectful interaction were found to be important factors determining willingness to recommend blood donation. Family members as well as friends are the preferred WOM-receivers and the personal face-to-face contact is the favored channel of communication. The results also show that WOM-behavior is strongly influenced by factors such as age, gender and donation frequency. By helping blood bank managers to better understand how WOM affects donation intention and behavior, this study provides a new approach to attract blood donors.